The history of the examination for state of alcohol intoxication - T. O. Barinskaya; A. A. Burtsev; A. V. Smirnov; A. E. Petukhov (Сеченовский вестник, 2011)
Evolution of the approaches to diagnostics of DUI as the evidentiary base in law violations is traced; parallelism in the development of scientiﬁc beliefs on the nature of acute alcohol intoxication, scientiﬁc and technological achievements – on one hand, and legislation in the ﬁeld of traﬃc safety, on the other is described Two principles of diagnostics are compared – clinical and chemical-toxicological, their advantages and disadvantages. Author’s point of view concerning optimal principles of diagnostics and legislation in Russia is formulated.